Nutrient leaching in extensive green roof substrate layers with different configurations - Xu, Chen; Liu, Zaohong; Cai, Guanjun; Zhan, Jian (Environmental science and pollution research international, 2022)
Due to substrate layers with different substrate configurations, extensive green roofs (EGRs) exhibit different rainfall runoff retention and pollution interception effects. In the rainfall runoff scouring process, nutrient leaching often occurs in the substrate layer, which becomes a pollution source for rainwater runoff. In this study, six EGR devices with different substrate layer configurations were fabricated. Then, the cumulative leaching quantity (CLQ) and total leaching rate (TLR) of NH 4 + , TN, and TP in the outflow of nine different depth simulated rainfall events under local rainfall characteristics were evaluated and recorded. Furthermore, the impact of different substrate configurations on the pollution interception effects of EGRs for rainfall runoff was studied. Results show that a mixed adsorption substrate in the EGR substrate layer has a more significant rainfall runoff pollution interception capacity than a single adsorption substrate. PVL and PVGL, as EGRs with layered configuration substrate layers, exhibited good NH 4 + -N interception capacity. The CLQ and TLR of NH 4 + -N for PVL and PVGL were − 114.613 mg and − 63.43%, − 121.364 mg, and − 67.16%, respectively. Further, the addition of biochar as a modifier significantly slowed down the substrate layer TP leaching effect and improved the interception effect of NH 4 + -N and TN. Moreover, although polyacrylamide addition in the substrate layer aggravated the nitrogen leaching phenomenon in the EGRs’ outflow, but the granular structure substrate layer constructed by it exhibited a significantly inhibited TP leaching effect.